Maxim Violations as Narrative Suspense Strategies in Murder on the Orient Express (2017) - Hudayashfa Qurrotun Na’ma; Almira Irwaniyanti Utami (Universitas Islam Negeri Palopo, 2026)
This study investigates how Gricean maxim violations function as a strategy for constructing narrative suspense in Murder on the Orient Express (2017). While previous studies on maxim violations in film discourse have primarily focused on classification and communicative functions, this study examines their role in narrative structure. Drawing on Grice’s Cooperative Principle and narrative suspense theories proposed by Sternberg and subsequent narratological studies, the study aims to identify the types of maxim violations and analyze their contribution to suspense construction. Employing a qualitative descriptive design with a pragmatic–narrative approach, the study analyzes 89 utterances from investigation scenes in the movie script, focusing on suspects’ interrogative interactions. The findings indicate that maxim violations function systematically as mechanisms for regulating information and maintaining uncertainty in detective narratives, with Quality violations occurring most frequently. The study demonstrates that conversational deviations operate not only as pragmatic phenomena but also as narrative resources in cinematic storytelling. These findings contribute to pragmatics, narrative discourse, and film studies by providing an integrative perspective on the relationship between language, information management, and suspense construction.